I married an ebay maniac - Perry, Jayne (Que Pub., 2006)
Has your spouse been spending more and more time on the computer? Do they hide the screen when you walk in the room? Have new items been appearing in your house while your older possessions seem to disappear? Perhaps the explanation is in "it"--EBay mania! I Married an eBay Maniac offers a glimpse into the world of eBay. Get up to speed on the basics of buying and selling on eBay, and find how to bring every family member to eBay so that you no longer have to eat dinner with your spouse clicking away on the keyboard. Turn their obsession into a family affair. This book describes how to play off one another's strengths and weaknesses, how to divide tasks to maximize efficiency, fun, and profits, and how to arrange a household to separate eBay from the non-eBay life. You'll be able to keep frustration levels down and income levels high1 With tips, tricks, and insight from an experienced eBayer, this book shows how much family fun and income can be had when the Maniac is no longer alone